A Slow Life History is Related to a Negative Attitude towards Cousin Marriages: A Study in Three Ethnic Groups in Mexico. (1st April 2013) - Buunk, Abraham P.; Hoben, Ashley D.
Little is known about current attitudes towards cousin marriages. Using data from a rural population in the Mexican state of Oaxaca, the present research examined how life history was related to attitudes towards cousin marriages in various ethnic groups. Participants were 205 parents from three ethnic groups. i.e., Mestizos (people of mixed descent, n = 103), indigenous Mixtecs ( n = 65), and Blacks ( n = 35). Nearly all men in this study were farm workers or fishermen. Participants reported more negative than positive attitudes towards cousin marriage, and women reported more negative attitudes than did men. The main objection against marrying a cousin was that it is wrong for religious reasons, whereas the risk of genetic defects was considered relatively unimportant. Cousin marriage was not considered to contribute to the quality and unity of marriage and the family. The three ethnic groups did not differ in their attitude towards cousin marriages. However, a slower life history was related to a more negative attitude towards cousin marriages, especially among Blacks, less so among Mixtecs, and not at all among Mestizos. In addition, and independent of the effect of life history, with increasing levels of parental control over mate choice, the attitude towards cousin marriage was more positive, but among men the attitude was more negative the more religious they were. The results are discussed in the context of theorizing on life history theory and the benefits and costs of cousin marriages.